Your inner fish : a journey into the 3.5-billion-year history of the human body - Shubin, Neil (2009)
Neil Shubin, a leading paleontologist and professor of anatomy who discovered Tiktaalik--the "missing link" that made headlines around the world in April 2006--tells the story of evolution by tracing the organs of the human body back millions of years, long before the first creatures walked the earth. By examining fossils and DNA, Shubin shows us that our hands actually resemble fish fins, our head is organized like that of a long-extinct jawless fish, and major parts of our genome look and function like those of worms and bacteria.--From publisher description
Finding your inner fish -- Getting a grip -- Handy genes -- Teeth everywhere -- Getting ahead -- The best-laid (body) plans -- Adventures in bodybuilding -- Making scents -- Vision -- Ears -- The meaning of it all -- Epilogue
Originally published: New York : Pantheon Books, 2008
Includes bibliographical references and index
Keywords: Human anatomy -- Popular works; Human evolution -- Popular works; Anatomy, Comparative; Biological Evolution; Phylogeny; Popular Work; Popular works; Popular works